2022
DOI: 10.17221/215/2022-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant growth regulators on potato tuber yield and quality

Abstract: The aim of the study conducted in 2019–2021 was to determine the effect of biostimulants and growth regulators on the yield size and structure, as well as the chemical composition of edible potato tubers. The cultivar evaluated was Vineta. Asahi SL, Kelpak SL, Aminoplant, Tytanit, gibberellic acid (GA3) and Moddus 250 EC were applied in potato cultivation. The application of biostimulants Asahi SL and Tytanit increased the total and marketable tuber yield, as well as the average tuber weight. Aminoplant had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…These findings have recently been confirmed by Nuraini [20] reporting that GA3 biosynthesis was reduced up to 60%, resulting in an increase in tuber formation by 40% when the potato crops were sprayed with a mixture of paclobutrazol and cytokini. An increase in tuber formation was also reported by Kołodziejczyk M & Gwóźdź [23] when potato crops were sprayed with plant growth regulator. Note: number at the same column followed by the same letter were significantly not different.…”
Section: Application Timesupporting
confidence: 70%
“…These findings have recently been confirmed by Nuraini [20] reporting that GA3 biosynthesis was reduced up to 60%, resulting in an increase in tuber formation by 40% when the potato crops were sprayed with a mixture of paclobutrazol and cytokini. An increase in tuber formation was also reported by Kołodziejczyk M & Gwóźdź [23] when potato crops were sprayed with plant growth regulator. Note: number at the same column followed by the same letter were significantly not different.…”
Section: Application Timesupporting
confidence: 70%
“…The highest yield of large tubers (Figure 3) of potato was also recorded with this method of weed control in potato plantation (object 5). Kołodziejczyk and Gwóźdż [21], after the application of the biostimulant Asahi SL, reported an increase in the marketable yield of 6.8 tha −1 . Gugała et al [12] found that, in plots sprayed with a herbicide or a herbicide and a biostimulant, the average yield of potato tubers was 13.6 to 33.2% higher compared to the control object protected only mechanically.…”
Section: Mechanical and Chemical Treatments Withmentioning
confidence: 99%
“…The biostimulants increase the efficiency of nutrient utilization and the tolerance to abiotic stress and improve the quality of crops [18]. The biologically active substances contained in these bio-preparations have a positive effect on plant growth, root system development and potato yield [19][20][21]. The growth regulators significantly reduced the symptoms of Phytophthora infestans infection and significantly increased the tuber yield [22].…”
Section: Introductionmentioning
confidence: 99%
“…Gugala et al [35] also found that the combinations of linuron + clomazone and metribuzin with seaweed extracts and nitrophenol biostimulants can increase the glycoalkaloids (TGA) in potatoes, when applied in separate applications. Seaweed extracts and nitrophenol biostimulants have been compared in a study that evaluates how they influence potato growth, while the weed control for this experiment was conducted using metribuzin + flufenacet (inhibitor of very long-chain fatty acids synthesis) [36]. Their results varied over the years and the treatments; one possible explanation is that the herbicide substances that were used, interacted with the tested biostimulants.…”
Section: Interaction Effects On Biostimulant and Herbicidal Efficacymentioning
confidence: 99%